(untitled) (Fiep Bulletin - online, 2013)
Apparently easy of being measured, the use of the Heart Hate was popularized as a tool for knowing the intensity zone training. But everybody knows that use the correct % of heart hate for practices the activity becomes necessary for we can optimizes the training with a correct control and minimizes the risks of some sort of accident. OBJECTIVE: The objective study it was to compare the reply of the Heart Hate in Maximum effort test in treadmill and compare with 3 regression equations for prediction of the maximum Heart Hate. METHODOLOGY: The present study it is descriptive type research with comparative character. It was chosen 37 individuals healthful with 27,49 ± 6,77 years average age. The 3 regression equations for prediction of the maximum Heart Hat used in the study had been” Karvonen”, Tanaka and Inbar, all equations for healthful masculine individuals. RESULTS: Test = 188,27 bpm; 220 - idade= 192,51*bpm; Imbar= 186,97 bpm and Tanaka= 187,76 bpm. CONCLUSION: Can be observed that was significant difference (p<0,05) when compared the averages between Heart Hate gotten in the test with the Karvonen and Imbar equation’s. With the Tanaka showing the result closes to the value reached in the test.